2006
DOI: 10.2174/138161206777585111
|View full text |Cite
|
Sign up to set email alerts
|

The Voltage-Dependent Anion Channel (VDAC): Function in Intracellular Signalling, Cell Life and Cell Death

Abstract: Research over the last decade has extended the prevailing view of mitochondria to include functions well beyond the critical bioenergetics role in supplying ATP. It is now recognized that mitochondria play a crucial role in cell signaling events, inter-organelle communication, aging, many diseases, cell proliferation and cell death. Apoptotic signal transmission to the mitochondria results in the efflux of a number of potential apoptotic regulators to the cytosol that trigger caspase activation and lead to cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
337
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(347 citation statements)
references
References 248 publications
(441 reference statements)
10
337
0
Order By: Relevance
“…In this study, the authors suggested that the effect of tBID on OMM permeabilization is through another unidentified OMM protein. The importance of VDAC for OMM permeabilization is further supported by recent evidence that overexpression of VDAC induces apoptosis in various cell types, and this effect is inhibited by BCL-2 and VDAC inhibitors [28,29].…”
Section: The Involvement Of Vdac In Apoptosismentioning
confidence: 75%
“…In this study, the authors suggested that the effect of tBID on OMM permeabilization is through another unidentified OMM protein. The importance of VDAC for OMM permeabilization is further supported by recent evidence that overexpression of VDAC induces apoptosis in various cell types, and this effect is inhibited by BCL-2 and VDAC inhibitors [28,29].…”
Section: The Involvement Of Vdac In Apoptosismentioning
confidence: 75%
“…More recently it has become clear that the permeability of the OMM is actually regulated by the channels that transport these molecules, the VDACs (40). In 1979 it was predicted that these channels would be involved in regulating mitochondrial metabolism (41), and numerous studies in the ensuing decades have proven this prediction to be true (42)(43)(44)(45)(46). The name of the channel is somewhat misleading, because although it originally was thought to be anion selective, VDAC also has been shown to transport cations such as calcium and numerous small metabolites including ATP, ADP, NADH, pyruvate, and others (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…The assignment of three residues in the N-terminal helix (K12, D16, and V17) benefited from the chemical shift information obtained from solidstate NMR (24). In total, five residues are assigned in the second half of the N-terminal helix (residues [12][13][14][15][16][17][18][19][20], demonstrating that this region is not broadened beyond detection by intermediate chemical exchange. This result is in line with the observation that peaks corresponding to residues A2-V17 give rise to distinct narrow crosspeaks in solid state NMR spectra of hVDAC1 reconstituted in liposomes, indicating a rather rigid conformation (24).…”
Section: μS-ms Dynamics Are Significantly Increased For the N-terminamentioning
confidence: 99%
“…Metabolite flow is regulated by a voltage-dependent conformational change between a high-conductance anionselective state, several low-conductance states favoring small cations (17,18), and a high-conductance cation-selective state (19). VDAC gating is furthermore modulated by a variety of ions, small molecules, apoptotic proteins of the Bcl-2 family, and hexokinase (20), strongly implicating VDAC's function in apoptosis regulation (21). To enable interactions and gating between various states, conformational variability of VDAC is expected.…”
mentioning
confidence: 99%